Analysis of an Inhomogeneously Loaded Helical Slow-Wave Structure for Broad-Band TWT's - Kapoor S.; Raju R.S.; Joshi S.N.; Gupta R.K.; Basu B.N. (My University, 2025)
In this paper, a potentially broad-band inhomogeneously loaded helical slow-wave structure is analyzed. The structure consists of a helix supported by a number of dielectric rods in a metal envelope. The supports considered here are not of conventional goemetry of rectangular, circular or wedge cross sections; rather, the two types of configurations studied in this paper are half-moon shaped and double-curved rods. The theoretical dispersion characteristics are compared with Belohoubek's published experimental results and are found to be in fairly good agreement. © 1989 IEEE